Hospital-dia: interfaces de uma nova clientela - Maia, Rochele Mendes (2004)
The mental Health is presenting if as a theme plenty instigate that divided public in the thinking forms and of leading practices of working with being psychic suffering. This study has for objective to trace the patienfs profíle attended by a private Hospdal-day (HD), in the period between May of 2001 to September of 2003, trying to identify the personal and socioeconomic aspects of the patients, collecting Information since the implantation of the electronic handbook until September of 2003 and taken conducts of 172 patients, searching of describes the scenery of the hospital-day with its intervention routines. This study of the exploratory-descriptive nature with quantitative approach, was realized in the municipal districts of Fortaleza-Ce, in a HD liked with a institution that renders cares to the ciientele formed by patients with psychic suffering. The collected data were always analyzed reflexively, your relationship with the bibfiography on the thematic. The work culminated in graphs e pictures distributed among the thematic: characterization of the place of HD; the patient attended by HD: show the face of the consumers, We notice that the proposal techinique of the researched Hospital-ay in consonance with the estabilished norms for the psychiatric attendance. This rearch turns possible that we know intrinsic aspects of the psychiatric attendance. This rcscarch turns possible that we know intrinsic aspects of the fundamental importance for the use of Services and knowledges that can maximized the benefít to the human being.